The criteria of sports editorial newsworthiness in journalism of printed Amapá - Sardinha, Antonio (2018)
This work aims to analyze the contents of the editors of Sports Amapá newspapers The Gazette and Journal of the Day. For observation, became scoped editions of the period of September, October and November 2014 at a daily. It was used as a method Content Analysis (Bardin), from the study of newsworthiness criteria, Galtung and Ruge's. The research contributes to understanding of the press working dynamics within the country. It appears that the approach made by the vehicles in question does not constitute a picture of the reality of local practices related to the sports world, characterized by a cover which includes themes related to sport, playing back content from other newspapers and/or agencies and ignoring the demand of the state sports sector.